2017
DOI: 10.1111/jan.13441
|View full text |Cite
|
Sign up to set email alerts
|

Barrier‐free communication in maternity care of allophone migrants: BRIDGE study protocol

Abstract: ClinicalTrials.gov ID: BernUAS NCT02695316.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This exploratory, qualitative study was designed to reveal processes, interpretive frames, and patterns of communication barriers from multiple perspectives using focus group discussions (FGD; Krueger & Casey, ) and problem‐centred interviews (Witzel, ). It was part of a broader investigation into allophone migrant women's access to maternity care (Origlia Ikhilor et al, ); detailed information on that study's methodology is described there. In the study for this article, we used the consolidated criteria framework for reporting qualitative studies (COREQ; Tong, Craig, & Sainsbury, ).…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This exploratory, qualitative study was designed to reveal processes, interpretive frames, and patterns of communication barriers from multiple perspectives using focus group discussions (FGD; Krueger & Casey, ) and problem‐centred interviews (Witzel, ). It was part of a broader investigation into allophone migrant women's access to maternity care (Origlia Ikhilor et al, ); detailed information on that study's methodology is described there. In the study for this article, we used the consolidated criteria framework for reporting qualitative studies (COREQ; Tong, Craig, & Sainsbury, ).…”
Section: The Studymentioning
confidence: 99%
“…Focus group members were informed of the need to preserve the confidentiality of group discussions. The ethical considerations were set out in detail in the study protocol (Origlia Ikhilor et al, ) and the ethics committee responsible issued a formal memorandum that no special Research Ethics Committee approval was necessary.…”
Section: The Studymentioning
confidence: 99%
“…The neglect of woman-centred care among women asylum seekers might be due to the phenomenon in industrialized countries that pregnant women of low socio-economic status are not comprehensively informed by their healthcare providers about having a choice in maternity care services, such as midwifery services or antenatal classes [ 45 ]. They therefore tend to comply with the prevailing medical or public clinical care model, which does not meet their special needs and can lead to worse perinatal outcomes [ 27 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interpreters provide essential services to physicians, which, e.g., aids in obtaining patient histories [ 27 , 53 ]. In our study we found that the unavailability of interpreter services in the standard healthcare model severely impacted the ability to conduct a clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation